Age-specific PSA reference ranges in Chinese men without prostate cancer - Liu, Zhi-Yong (Nature Publishing Group, 2009)
This study is to determine age-specific prostate-specific antigen (PSA) distributions in Chinese men without prostate cancer (PC) and to recommend reference ranges for this population after comparison with other studies. From September 2003 to December 2006, 9 374 adult men aged from 18 to 96 years agreed to participate in the study. After all cases of PC were excluded, 8 422 adult men participated in statistical analysis and were divided into five age groups. Simple descriptive statistical analyses were carried out and quartiles and 95th percentiles were calculated for each age group. The age-specific PSA reference ranges are as follows: 40–49 years, 2.15 ng mL(−1); 50–59 years, 3.20 ng mL(−1); 60–69 years, 4.10 ng mL(−1); 70–79 years, 5.37 ng mL(−1). The results indicate that the ethnic differences in PSA levels are obvious. The currently adopted Oesterling's age-specific PSA reference ranges are not appropriate for Chinese men. The reference ranges of this study should be more suitable to Chinese men.